Determination of Caffeine Content in Green Coffea liberica Beans by UV–Visible Spectrophotometry and Evaluation of Its Effect on Weight Reduction - Danik Sulistyoningsih; Firstca Aulia Rachma; Silvy Aldila; Suksi Riani; Winnie Kristiyanti; Recta Syifa Dwimart (INDO PUBLISHING, 2026)
Background: Green coffee beans (Coffea liberica) are a rich source of bioactive compounds, including caffeine, chlorogenic acid, flavonoids, and polyphenols, which have potential health-promoting properties. Caffeine has been reported to enhance thermogenesis, stimulate fat oxidation, and increase energy expenditure, making it a promising natural compound for weight management. This study aimed to determine the caffeine content of green Coffea liberica beans using UV–Visible spectrophotometry and to evaluate the implementation of green coffee extract consumption on body weight reduction. Methods: An experimental study was conducted by extracting green coffee beans with 96% ethanol followed by phytochemical screening and quantitative determination of caffeine using UV–Visible spectrophotometry at a maximum wavelength of 272 nm. The analytical method was validated by assessing linearity, accuracy, and precision. A one-group pretest–posttest design was employed to evaluate the implementation of green coffee extract in overweight adults with a body mass index (BMI) ≥25 kg/m². Body weight was measured before and after the intervention, and statistical analysis was performed at a 95% confidence level. Results: The spectrophotometric method demonstrated satisfactory linearity, accuracy, and precision, indicating its suitability for caffeine determination. Green Coffea liberica beans were confirmed to contain caffeine and other bioactive compounds that contribute to antioxidant activity. Consumption of green coffee extract showed a tendency to reduce body weight following the intervention period. Conclusion: UV–Visible spectrophotometry is a reliable method for determining caffeine content in green Coffea liberica beans. The presence of caffeine and other bioactive compounds supports the potential application of green Liberica coffee as a functional food ingredient for weight management.